Why Islam (Properly Understood) Is the Solution: Reflections on the Role of Religion in Tunisia’s Democratic Transition (American Journal of Islam and Society, 2013)
This paper is a provocative play on the famous Muslim Brotherhoodslogan al-Islām hūwa al-ḥāl (Islam is the solution). Whilecritics of the Muslim Brothers rightly criticized them for the simplicityof their worldview in thinking that religion was a panaceafor all of the problems confronting Muslim societies during thelate twentieth century, an argument can be made that religion doesprofoundly matter in the context of the struggle for democracy inthe Arab-Islamic world. In the aftermath of the Arab Spring, democratictransitions in North Africa and the Middle East will be dependenton democratically negotiating the question of religion’srole in politics. Here I provide some reflections on this topic witha focus on Tunisia’s transition to democracy.